2019
DOI: 10.1101/602938
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The MyMOMA domain of MYO19 encodes for distinct Miro-dependent and Miro-independent mechanisms of interaction with mitochondrial membranes

Abstract: for critical reading and discussions related to this manuscript. Hypotheses and experiments in this study were conceived by OAQ. Experiments were performed by JLB, BMF, NRM, JMC, ELS, TYT, and OAQ.Data analysis and manuscript preparation were completed by JLB, BMF, NRM, JMC, TYT, MBM, and OAQ. Except for the proteomics analysis, all experiments for the initial submission were completed during the 10-week 2018 summer research session at University of Richmond. We would also like to that Edward Salmon for his ex… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(23 citation statements)
references
References 112 publications
3
20
0
Order By: Relevance
“…Originally, Myo19 was thought to act as a peripheral membrane protein, interacting with lipids directly. However, recent work discovered that Miro1/2 are receptors for recruiting and stabilizing Myo19 to the mitochondria based on knockout studies of Miro1 and Miro2, in addition to proximity labeling approaches (Figure c,d). Biochemical studies demonstrated that the Myo19 tail contains both Miro1/2‐independent and Miro1/2‐dependent mitochondrial targeting sites .…”
Section: Miro Coordinates Mitochondrial Transport On Both Microtubulementioning
confidence: 99%
See 1 more Smart Citation
“…Originally, Myo19 was thought to act as a peripheral membrane protein, interacting with lipids directly. However, recent work discovered that Miro1/2 are receptors for recruiting and stabilizing Myo19 to the mitochondria based on knockout studies of Miro1 and Miro2, in addition to proximity labeling approaches (Figure c,d). Biochemical studies demonstrated that the Myo19 tail contains both Miro1/2‐independent and Miro1/2‐dependent mitochondrial targeting sites .…”
Section: Miro Coordinates Mitochondrial Transport On Both Microtubulementioning
confidence: 99%
“…However, recent work discovered that Miro1/2 are receptors for recruiting and stabilizing Myo19 to the mitochondria based on knockout studies of Miro1 and Miro2, in addition to proximity labeling approaches (Figure c,d). Biochemical studies demonstrated that the Myo19 tail contains both Miro1/2‐independent and Miro1/2‐dependent mitochondrial targeting sites . Interestingly, Miro1/2‐mediated recruitment is regulated by the nucleotide state of Miro1/2 N‐terminal GTPase domain .…”
Section: Miro Coordinates Mitochondrial Transport On Both Microtubulementioning
confidence: 99%
“…While stable subplasmalemmal actin rings form periodic structures that wrap around axons to support the axonal membrane, dynamic intra‐axonal filaments help to enrich actin at presynaptic terminals (Ganguly et al., 2015; Xu, Zhong, & Zhuang, 2013). It has been reported that mitochondrial receptors Miro1/2 regulate recruitment and stability of myosin‐19, thus likely coordinating MT‐ and actin‐based mitochondrial trafficking in mouse embryonic fibroblasts (MEFs) (Bocanegra et al., 2020; López‐Doménech et al., 2018; Oeding et al., 2018; Quintero et al., 2009). However, the role of myosin‐19 in axonal mitochondrial trafficking is not clear.…”
Section: Developmental Regulation Of Axonal Mitochondrial Motilitymentioning
confidence: 99%
“…Differential binding localization studies suggest that Miro1 and Miro2 interact differently with the motor adapters TRAK1 and TRAK2 (van Spronsen et al, 2013). The nGTPase domains of HsMiro1 and HsMiro2, which are believed to play the key role in the interactions with TRAK1/2 (Bocanegra et al, 2019;Oeding et al, 2018), are structurally quite similar, as they exhibit 73% sequence identity and 88% sequence similarity. Consequently, the set of 21 nonhomologous amino acid substitutions between them presumably differentiate the functions of the two proteins.…”
Section: Discussionmentioning
confidence: 99%